Atomistic simulations of dislocation plasticity in concentrated VCoNi medium entropy alloys: Effects of lattice distortion and short range order - Esfandiarpour, Amin; Alvarez-Donado, Rene; Papanikolaou, Stefanos; Alava, Mikko (Frontiers in Materials, 2022)
Face-centered cubic (fcc) high and medium entropy alloys (H/MEAs) have been shown to display superior mechanical properties at low temperatures, but significant improvement of their strength at high temperatures is required for industrial applications at extreme conditions. Recently, it has been shown that the breakthrough of the MEAs from equiatomic/near-equiatomic to non-equiatomic ratios leads to strong MEAs with good ductility. To design new H/MEAs, we consider two important factors that may influence strength: the chemical composition and chemical short range order (CSRO). In this study, we investigate the depinning stress ($σ_c$) as a criterion of strength of several compositions of VCoNi concentrated solid solution alloys (CSSAs) including V_{0.33}Co_{0.33}Ni_{0.33}, V_{0.35}Co_{0.2}Ni_{0.45} , V_{0.33}Co_{0.17}Ni_{0.5}, and V_{0.17}Co_{0.33}Ni_{0.5} at 5 K and 300 K, using atomistic simulations. The chosen interatomic potential is shown to be reliable by comparing experimental/ab initio values and calculated parameters such as lattice constant, shear modulus, depinning stress, and temperature variation of stacking fault width for equimolar VCoNi. We find a good agreement between experimental friction stress and the depinning stress extracted from our results for equimolar VCoNi. Also, we find that Vclusters are the main pinning points of dislocations, and With a random distribution of atoms, we find that the alloy composition V_{0.33}Co_{0.17}Ni_{0.5} displays the largest depinning stress at both 5 K and 300 K. Furthermore, to investigate how CSRO affects the strength of these alloys, we design CSRO into the microstructure using two different methods: In the first method, hybrid Molecular-dynamics/Monte-Carlo simulations were employed to simulate annealing at various temperatures.We observe that such simulations create CSRO so that it increases with decreasing annealing temperature. Recently, the CSRO motif and its concentration in an equimolar VCoNi have been determined by experiment. By modeling this experiment, we also implemented the CSRO into microstructure as the second method. By using both methods, the effect of CSRO on the magnitude of the depinning stress is discussed. It was shown that in both methods, CSRO significantly influences the strength of non-equimolar VCoNi alloys.